DISORDERS OF URODYNAMICS OF LOWER URINARY TRACTS IN TUBERCULOSIS SPONDYLITIS PATIENTS - A. N. Muravev; A. A. Lebedev; A. I. Gorbunov; N. V. Orlova; A. F. Semchenko (Туберкулез и болезни лёгких, 2015)
The prospective analysis was conducted covering urodynamic testing of 20 patients su|ering from active tuberculosis spondylitis having neurogenic disorders of urination and preparing for reconstructive surgery. The obtained data allowed detecting functional disorders which can cause irreversible changes of the upper and lower urinary tract, to complicate the post-surgery recovery and the consequent rehabilitation of these patients. The authors point out at certain limitations in using of one component of urodynamic testing – evaluation of evacuation capacity of the urinary bladder due to the existing neurologic disorders and spinal instability in the area of tuberculous lesion.